Pengaruh Penggunaan Smartphone terhadap Interaksi Sosial Siswa Kelas X - Ufiya Putri Adhiyati; Rosalina Dewi Heryani; Irna Kumala (Hayati : Jurnal Pendidikan, 2026)
The development of technology, particularly smartphone usage, has brought significant changes to daily life, including students’ social interaction patterns. Smartphones provide benefits by facilitating communication and expanding social connections through digital platforms. However, excessive use may reduce direct interactions within the surrounding environment. This study aimed to examine the influence of smartphone usage on Grade X students’ social interaction. This research employed a quantitative approach using a survey method and was conducted at Karya Bahana Mandiri 2 Vocational High School. The sample consisted of 74 students selected from a population of 90 students using the Yamane formula with a 5% error rate. Data were collected through observation and questionnaires. The results showed a simple linear regression equation of y = 11.704 + 0.623x. The correlation coefficient value of 0.613 indicated a strong relationship between smartphone usage and students’ social interaction. The coefficient of determination of 37.6% indicated that smartphone usage contributed to students’ social interaction, while the remaining 62.4% was influenced by other factors not examined in this study. The hypothesis testing results showed that the t-value (6.582) was greater than the t-table value (1.993), with a significance value of 0.00 < 0.05. Therefore, it can be concluded that smartphone usage has a significant influence on students’ social interaction.